Dampak Lingkungan Dan Kekerasan Sosial Terhadap Kesulitan Belajar Anak Sekolah Dasar - Zikriatul Ulya; Nur Maqfirah (Ali Institute of Research and Publication, 2022)
The impact of bullying on the learning difficulties of elementary school children is very influential. Because victims of bullying will interfere with their learning activities. How can he learn, he alone is psychologically difficult and uncomfortable. Victims of bullying will not be able to succeed in achieving education. This study uses a qualitative descriptive method and literature review of reading materials related to the researched. The results of this study indicate that 1) most of the samples have experienced or seen acts of bullying and violence in the school environment, 2) there are learning difficulties in students who experience acts of bullying and violence, 3) perpetrators who often commit acts of bullying and violence include friends. same age. Based on this research, it can be concluded that most elementary school students have experienced or seen bullying at school.